Caregiver burden among parents of school-age children with asthma: a cross-sectional study - Yang, Fang; Zhou, Jingru; Xiao, Hongying; Wu, Xia; Cui, Yingjuan; Huang, Houqiang; Zheng, Silin; Li, Huawei (Frontiers in Public Health, 2024)
Objective:To investigate the caregiver burden of parents of school-age children with asthma and analyze the factors influencing their caregiver burden.Methods:A convenience sampling method was used to select 366 parents of school-age children with asthma who visited the outpatient departments of three tertiary hospitals in Sichuan Province, China, from January 2021 to July 2021. A general information questionnaire and the Caregiver Burden Inventory (CBI) were used to assess the current caregiver burden and analyze the influencing factors.The caregiver burden score of parents of school-age children with asthma was 27 (17, 39), with 40.43% of parents experiencing moderate to high levels of burden. Detailed results of univariate analysis showed that there were significant differences in caregiver burden scores based on parents' gender, highest education level, number of children, occupation, family history of asthma, monthly family income, annual medical expenses for the child, child's gender, whether the child had undergone lung function tests, number of emergency visits due to asthma exacerbation in the past three months, and whether the child had missed school due to asthma exacerbation in the past three months (P ＜ 0.1). Detailed results of multivariate analysis showed that parents' gender, occupation, family history of asthma, monthly family income, annual medical expenses for the child, number of emergency visits due to asthma exacerbation in the past three months, and whether the child had missed school due to asthma exacerbation in the past three months were independent risk factors for caregiver burden in parents of school-age children with asthma (P＜0.05).Parents of school-age children with asthma experience a certain level of caregiver burden, with over one-third of parents experiencing moderate to high levels of burden. Being a mother, being a worker, having no family history of asthma, having low monthly family income, having high annual medical expenses for the child, having frequent emergency visits due to asthma exacerbation in the past three months, and having missed school due to asthma exacerbation in the past three months are independent risk factors for caregiver burden in parents of school-age children with asthma.